Language and ideology in english and vietnamese business hard news reporting - a comparative study - Vo, Duc Duy (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2013)
This paper reports on an investigation into how governments, central banks and people are presented in English and Vietnamese hard news, business reports. Drawing on the theoretical frameworks of Critical Discourse Analysis (CDA) and the transitivity system in Systemic Functional Linguistics (SFL), the study examined the underlying ideology embedded in the business news reports. The paper consists of two parts. The first part analyses two texts sharing the same topic which serves as a preliminary study to a corpus analysis of fifty texts (25 in each language) discussed in the second part. The analysis shows that the government and its central bank in the Vietnamese reports are portrayed as more powerful than those in the English reports, and people in Vietnamese are presented as passive and absent while those in English are presented as active, performing various roles in the experiential world of business. The study offers some implications for English language teaching practices.